Thai Students’ Difficulties in Mastering English Speaking at Mattayom 5 Darunsatwithaya School - Manal Chema; Syahrul Syahrul; Reflinda Reflinda; Widya Syafitri (Journal on Education, 2023)
Background of this study were based on the problems that occured in several students at Mattayom 5 Darunsat Withaya. They were several students did not speak naturally. Then, they were rare to practice their English speaking at school. Also, they did not use the body language when speaking English in front of the class. In addition, they were also doing eye contact with their friends. Of course, they were lack of confidence, lack of vocabulary mastery. Regarding to the problems above, it can be understood that they faced the difficulties in speaking English. Therefore, this study aimed to find out the causes of difficulties in mastering English speaking at Mattayom 5 Darunsat Withaya Islamic School. Furthermore, this type of study was quantitative descriptive. The data was collected through questionnaire. The total population used is more than 140 students. Because there were 100 students who have problems speaking English. Unfortunately, only 70 students filled out the questionnaire during data collection so that the sample of this study amounted to 70 students. Moreover, there were 2 causes why the students were difficult in speaking English. They were linguistic factor such as vocabulary, grammar, and pronunciation and psycholinguistic factor such as anxiety and shyness. In this result, vocabulary was dominant causes for students in speaking English. It can be seen that the highest of vocabulary factor was lack of vocabulary. It was 57% that they had lack of vocabulary.